COVID-19 Pandemic: What is Known Till June 2020 and What is Yet to Know? - Piryani, R.M.; Piryani, S.; Piryani, S.; Dangal, G.; Shah, J.N. (Kathmandu University Medical Journal, 2020)
Since first cluster of unknown pneumonia from China reported in December 2019 to World Health Organization, more than 10.5 million new cases and more than 0.513 million deaths have been reported till June 30, 2020 in six months’ time. World got to know lot of facts about COVID-19 within short period of six months and success stories too concerning its containment. The situation has constantly been unfolding every moment educating people regarding public health and clinical aspects of the infection and disease and its impact on countries and communities. But still lot of information and evidences are required with regard to pharmacological interventions including effective drugs and efficacious vaccine to mitigate the impact of COVID-19 pandemic at all levels. It seems that we have to live with COVID-19 months-years as the virus is going to stay for longer period of time. The option is to continue practice of effective non-pharmacological interventions as to minimize spread of COVID-19 and ensure adequate provision of PPE to healthcare workforce and testing of health-care workers (HCWs) as to alleviate the anxiety of HCW and lessen their depletion by unnecessary quarantine thereby protect their health and reduce in hospital transmission.